Burch colposuspension. Issue 2 (8th January 2019) - Veit‐Rubin, Nikolaus; Dubuisson, Jean; Ford, Abigail; Dubuisson, Jean‐Bernard; Mourad, Sherif; Digesu, Alex
Abstract : Aims: To evaluate the historic and pathophysiologic issues which led to the development of Burch colposuspension, to describe anatomic and technical aspects of the operation and to provide an update on current evidence. Methods: We have performed a focused literature review and have searched the current available literature about historic dimension, technical descriptions, and efficacy of Burch colposuspension. Results: Burch colposuspension, performed either by an open or a laparoscopic approach, is an effective surgical treatment for stress urinary incontinence. Conclusions: In current recommendations, Burch colposuspension remains an option for secondary treatment. Because midurethral slings have recently become under scrutiny, it may return as a first‐line treatment procedure. Both open and laparoscopic Burch colposuspension should therefore nowadays be provided in fellowship programs worldwide.